ENVIRONMENTAL PRESERVATION AND SOCIAL RESPONSIBILITY: A UNIVERSITY EXTENSION EXPERIENCE AT THE CÓRREGO DA SERRA PROJECT (CIPEEX, 2025)
This text describes a university extension activity, proposed by the course Citizenship, Ethics, and Spirituality and conducted in the second semester of 2024, which focused on environmental preservation and the promotion of social responsibility, aiming to raise community awareness about the importance of environmental conservation. This activity took place at the headquarters of the Córrego da Serra Project, in Rubiataba, Goiás, founded on January 9, 2003, and located along the GO-334 highway, an initiative dedicated to environmental preservation and the defense of social rights, integrating community engagement and local sustainability. The main objective of the activity was to sensitize the community regarding the impacts of environmental degradation, such as pollution, deforestation, and inadequate management of natural resources, while encouraging the adoption of sustainable practices and active citizenship. The methodology included prior planning of actions, meetings with the team and local partners, community mobilization through social media and direct invitations, a technical visit to the creek to observe environmental conditions and record issues of pollution and degradation, and a “Roda de Conversa” (discussion circle) with the local population, teachers, and environmental professionals to discuss preservation strategies and concrete actions. The results showed a significant increase in environmental awareness among participants, strengthened community engagement, and the initiation of partnerships for the continuation of creek recovery actions, in addition to the development of academic and professional skills such as leadership, teamwork, organization, communication, and ethical decision-making. The experience also encouraged reflections on the interdependence between ethics, citizenship, and sustainability, demonstrating that responsible practices in organizational and community contexts are essential for collective well-being and environmental preservation. Among the challenges faced were community mobilization and the management of time and resources, overcome through detailed planning, effective communication, and team collaboration. It is concluded that extension activities like this provide practical learning, create meaningful social impact, and reinforce the importance of integrating social responsibility actions into natural resource management, encouraging future administrators to act with ethics, responsibility, and commitment to sustainable development. The experience demonstrated that collective and well-planned initiatives are essential to promote positive change, raise environmental awareness, and ensure the continuity of sustainable practices within the community.
Keywords: Environmental Preservation; Social Responsibility; Citizenship; University Extension